Analysis of Factors that Influence the Comfort of Patients when Receiving Care in TK II dr. Soepraoen Hospital - Semiarto, Mufit; Peristiowati, Yuly; Koesnadi (Master of Public Health Program Universitas STRADA Indonesia, 2020)
Patient comfort while receiving hospital care services is one of the hallmarks of hospitals in competition. Health service needs and services related to patient needs must be able to be served easily, quickly, accurately, with quality and affordable costs. The purpose of this study was to determine the factors that influence patient comfort while receiving care at the TK II hospital Dr. Soepraoen. The research design used is quantitative research. The research method used is the survey method and documentation method. The sampling technique used proportional sampling with a sample of 100 respondents. Data analysis techniques using multiple linear regression tests. The results showed that the descriptive results of behavioral variables showed an overall average value of 4.16 with a percentage of 38% and good categories, descriptive spatial variables had an overall average value of 4.07 with a percentage of 45% with good categories, in the descriptive variable environment had a value the overall average of 4.06 is in the good category with a percentage of 36%, in the quality variable the health service has a mean overall score of 4.19 in the good category percentage of 61%, and in the variable patient comfort during treatment has an overall average value of 4 00 in the good category with a percentage of 68%. Based on the value of the determination coefficient obtained by the number 94.7%, it means that the contribution percentage of the effect of the independent variable of compensation which consists of behavior, spatial planning, environment, and service quality on the comfort dependent variable is 94.7%. Of the 100 respondents surveyed on employee behavior has a significant influence on comfort, in spatial planning has a significant influence on comfort, the environment has a significant influence on comfort, on service quality has a significant influence on comfort, and simultaneously for each each behavior, spatial, environmental, and service quality variables have a significant influence on comfort